Evaluation of Dyslipidaemia in Patients with Chronic Viral Hepatitis in a Lower Socio-Economic Country: Dyslipidaemia in Chronic Viral Hepatitis - Jabeen, Rakhshinda; Rehman, Aziz Ur; Mobin, Ahsan; Haroon, Hussain; Manzoor, Imtiaz; Ubaid, Muhammad (Pakistan Journal of Health Sciences, 2024)
Patients having chronic viral hepatitis do have disturbances in their serum lipid profiles, still the monitoring of dyslipidemia is not a routine part of management in low socio economic countries. Objective: To investigate the status of lipid profile among patients with chronic hepatitis and compare them with non-infected individuals. Methods: A cross-sectional study was done in a Tertiary Care Hospital of Karachi, from 5th September 2022 to 31st May 2023. Patients with chronic hepatitis B and C, diagnosed within two years with a body mass index (BMI) of 25-29.9 kg/m2 were included. Their comparison was done with non-infected individuals of the same BMI. All patients were evaluated with different parameters of lipid profile along with haemoglobin, alanine aminotransferase, albumin and international normalized ratio. Results: Among 521 participants of the study, the grouping was almost equal. The age range was 12-75 years, with an increased number of females in each group. In comparing the different statuses of lipid profile, each parameter including cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein, all were significantly much less in patients with chronic viral hepatitis as compared to controls with a p-value of 0.000 in all. Conclusions: It was concluded that Dyslipidaemia is not common among chronic viral hepatitis patients’ despite being overweight, particularly among patients with child’s class A.